Theoretical foundations of developing skills of future engineers in teaching the science of electrical, electronic systems and hydraulic equipment of machines to students of technical higher education institutions - Rakhimov Sarvar Ibrahimovich (Global Scientific Publishing, 2023)
In this article, the issues that are important in determining the priorities of the systematic reform of education in our country, and in raising the spiritual, moral and intellectual development of future specialists to a new level in terms of quality have been considered
Keywords: Education; method; interactive; expert